Demand-side determinants of Indonesian palm oil exports to major destination countries: Evidence from India, China, and Pakistan - Hodijah, Siti; Achmad, Erni; Emilia, Emilia; Mustika, Candra (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2025)
Palm oil is one of Indonesia’s leading export commodities and plays an important role in supporting export revenue and international trade performance. This study aims to analyze the development of Indonesian palm oil exports and examine the influence of gross domestic product (GDP), exchange rates, and population on Indonesian palm oil exports to its three major destination countries, namely India, China, and Pakistan, during the period 2012–2022. This study employed a quantitative approach using descriptive analysis and panel data regression. The findings show that Indonesian palm oil exports to the three destination countries fluctuated during the observation period, with India recording the highest average export value and Pakistan showing a stronger upward trend toward the end of the period. The regression results indicate that GDP and exchange rates have a positive and significant effect on Indonesian palm oil exports, while population has a significant negative effect. These findings suggest that destination-country macroeconomic conditions and price competitiveness play an important role in shaping Indonesia’s palm oil export performance. This study contributes to the international trade literature by providing comparative empirical evidence on the demand-side determinants of Indonesian palm oil exports across major destination countries. In addition, the findings offer practical insights for strengthening export competitiveness and developing export-oriented trade strategies in the global palm oil market.